METODE DAN PENDEKATAN PEMBUKTIAN WUJUD TUHAN: Studi Pemikiran Muhammad Iqbal dan Bediuzzaman Said Nursi - Maftukhin, Maftukhin; Khamami, Akhmad Rizqon (ULUL ALBAB Jurnal Studi Islam, 2018)
This article examines the approach of Muhammad Iqbal and Bediuzzaman Said Nursi in proving the form of God. Their approaches come in the mindset of the invasion of atheism and the philosophy of materialism. Both thinkers use different approaches. While Iqbal uncovered arguments of God from the aspect of epistemology and offered arguments for religious experience, Nursi used the teleological argument utilizing the development of science. Nursi used the form of God arguments inherited from earlier scholars to strike at the attacks of atheism and materialism. Whereas Iqbal used a philosophical approach learned from Western scientists. On the other hand, when Iqbal uncovered from an aspect of philosophy, Nursi used simple language to appeal to ordinary people by presenting teleological arguments in the form of stories, dialogues, analogies, arguments for natural order, and impossible arguments. These two thinkers use a different approach, but both of them use science as the basis of their arguments. Nursi used the latest findings of science in his day to reinforce the arguments he raised, while Iqbal used the epistemology of science to manifest God.